Calculation of the horizontal two-dimensional unsteady flows by the method of characteristics - Lich, Tran Gia; Son, Nguyen Minh; Cuong, Le Viet (Vietnam Journal of Mechanics, 2003)
This paper will be concerned with the characteristic form of the two dimensional Saint-Venant equation system, the supplementary equations at the boundaries, the methods of characteristics for solving the equation system and some numerical experiments.